2016
DOI: 10.1161/circheartfailure.114.001937
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spironolactone on Longitudinal Changes in Health-Related Quality of Life in the Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist Trial

Abstract: Background— Heart failure (HF) with preserved ejection fraction patients have equally impaired health-related quality of life (HRQL) compared with those with HF with reduced ejection fraction, but limited studies have evaluated the impact of therapies on changes in HRQL. Methods and Results— Patients ≥50 years of age, with symptomatic HF and left ventricular ejection fraction ≥45%, were enrolled in Treatment of Preserved Cardiac Function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 36 publications
(38 reference statements)
2
69
0
Order By: Relevance
“…14 There was no significant reduction in the primary outcome with spironolactone, when added to standard medical therapy in the overall population, although there was a significant improvement in the KCCQ Overall Summary score (KCCQ-os). 5 In TOPCAT, however, there were concerns about the validity of data from patients enrolled in Russia and Georgia (48.7% of trial population, 15,16 so we decided, a priori , to exclude patients from Russia and Georgia (n=1,678) in the current analyses, leaving a final analytic cohort from TOPCAT of 1,372 patients (Figure 1). …”
Section: Methodsmentioning
confidence: 99%
“…14 There was no significant reduction in the primary outcome with spironolactone, when added to standard medical therapy in the overall population, although there was a significant improvement in the KCCQ Overall Summary score (KCCQ-os). 5 In TOPCAT, however, there were concerns about the validity of data from patients enrolled in Russia and Georgia (48.7% of trial population, 15,16 so we decided, a priori , to exclude patients from Russia and Georgia (n=1,678) in the current analyses, leaving a final analytic cohort from TOPCAT of 1,372 patients (Figure 1). …”
Section: Methodsmentioning
confidence: 99%
“…However, secondary and post hoc analyses revealed that MR antagonism improved quality of life in patients with HFpEF (Lewis et al. 2016) and reduced hospitalization and mortality in those enrolled in the Americas (rather than Eastern Europe) (Pfeffer et al. 2015; Bristow et al.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) study, a large randomized, double-blind clinical trial of spironolactone versus placebo in patients with symptomatic HFpEF, did not achieve a significant reduction in the primary composite outcome of time to cardiovascular death from cardiovascular causes, aborted cardiac arrest, or hospitalization for management of HF; however, TOPCAT did demonstrate that spironolactone decreases HF hospitalizations in HFpEF patients (118). Use of spironolactone for HFpEF was associated with an improvement in HF-specific health-related quality of life (119) and, in a separate study, improved exercise tolerance (120). Actually, the beneficial effects of spironolactone in HFpEF may be more significant.…”
Section: Potential Targets or Approachesmentioning
confidence: 99%